2008
DOI: 10.2746/042516408x250184
|View full text |Cite
|
Sign up to set email alerts
|

The effect of induced hindlimb lameness on thoracolumbar kinematics during treadmill locomotion

Abstract: Even subtle lameness can result in changes in back kinematics, which emphasises the intricate link between limb function and thoracolumbar motion. It may be surmised that, when chronically present, subtle lameness induces back dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 21 publications
6
44
1
Order By: Relevance
“…Work in horses demonstrated that subtle lameness had no effect on stride length at walk (Buchner et al, 1996;Gomez Alvarez et al, 2008) or trot (Gomez Alvarez et al, 2008), as also demonstrated in dairy cows by Telezhenko and Bergsten (2005) and confirmed by the current study. More severe lameness causes (e.g., SU does seem to affect stride length more; Flower et al 2005).…”
Section: Relationship Between Locomotion Score and Kinematic Gait Anasupporting
confidence: 89%
“…Work in horses demonstrated that subtle lameness had no effect on stride length at walk (Buchner et al, 1996;Gomez Alvarez et al, 2008) or trot (Gomez Alvarez et al, 2008), as also demonstrated in dairy cows by Telezhenko and Bergsten (2005) and confirmed by the current study. More severe lameness causes (e.g., SU does seem to affect stride length more; Flower et al 2005).…”
Section: Relationship Between Locomotion Score and Kinematic Gait Anasupporting
confidence: 89%
“…This is in contrast to suggestions that in lame horses the tuber coxae on the lame side may 'hinge' over an almost stationary tuber coxae on the sound side (Buchner et al, 1996), but matches previous empirical findings showing no significant effect of mild lameness on pelvic rotation symmetry (Gomez-Alvarez et al, 2008). The asymmetry progression with increasing lameness for the tubera coxae on both, the sound and lame side, matched discrete experimental observations (Buchner et al, 1996): while asymmetry of the tuber coxae on the lame side increased continuously, the tuber coxae on the 'sound' side passed through a stage of reduced asymmetry and movement range (compare Fig.…”
Section: Can a Simple Rigid Body Model Based On Symmetrical Pelvic Rocontrasting
confidence: 54%
“…While research efforts are greatest in the human domain (Whittle, 1996;Simon, 2004;Wren et al, 2011), gait analysis in horses is also receiving significant interest (Keegan, 2007): with most horses being not only a companion animal but also an athlete, locomotor soundness is crucial for this species. Evidence for movement adaptations associated with equine lameness is presently generated by sampling empirical data, often from less than 20 horses, either by causing lameness through intervention (Buchner et al, 1996;Gomez-Alvarez et al, 2008) or by sampling data from animals admitted to veterinary institutions (May and Wyn-Jones, 1987;Peham et al, 2001;Audigie et al, 2002;Church et al, 2009;Keegan et al, 2010). In the light of the mounting observations and conclusions drawn from such discrete experimental findings that are already forming the foundation for evidence-based lameness detection, we propose that it is now time to test and deduce, rather than induce, expected gait changes and to understand field observations in the context of the underlying mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Hindlimb lameness alters movement of the back (Gomez Alvarez et al . ) and horses with concurrent lameness and/or thoracolumbar pain may be more likely to develop SI joint region pain due to compensatory gait alterations (Buchner et al . ).…”
Section: Discussionmentioning
confidence: 99%